In Vivo Quantitative Measurement of Arthritis Activity Based on Hydrophobically Modified Glycol Chitosan in Inflammatory Arthritis: More Active than Passive Accumulation - Kyeong Soon Park; Jin Hee Kang; Keum Hee Sa; Hee Beom Koo; Hyun Jung Cho; Eon Jeong Nam; In Chan Youn; Kwang Meyung Kim; In San Kim; Ick Chan Kwon; Kui Won Choi; Young Mo Kang (Molecular Imaging)
We demonstrated that arthritis could be visualized noninvasively using hydrophobically modified glycol chitosan nanoparticles labeled with Cy5.5 (HGC-Cy5.5) and an optical imaging system. Activated macrophages expressing Mac-1 molecules effectively phagocytosed HGC-Cy5.5, which formed spherical nanoparticles under physiologic conditions. We estimated the applicability of HGC-Cy5.5 to quantitative analysis of arthritis development and progression. Near-infrared fluorescence images, captured after HGC-Cy5.5 injection in mice with collagen-induced arthritis, showed stronger fluorescence intensity in the active arthritis group than in the nonarthritis group. According to the progression of arthritis in both collagen-induced arthritis and collagen antibody-induced arthritis models, total photon counts (TPCs) increased in parallel with the clinical arthritis index. Quantitative analysis of fluorescence after treatment with methotrexate showed a significant decrease in TPC in a dose-dependent manner. Histologic evaluation confirmed that the mechanism underlying selective accumulation of HGC-Cy5.5 within synovitis tissues included enhanced phagocytosis of the probe by Mac-1-expressing macrophages as well as enhanced permeability through leaky vessels. These results suggest that optical imaging of arthritis using HGC-Cy5.5 can provide an objective measurement of disease activity and, at the same time, therapeutic responses in rheumatoid arthritis.